Shaping Perceptions: A Study of Ukraine and Ukrainians in Slovak Media throughout Two Years of War - Mariana Kitsa (Communication Today, 2025)
This article presents the results of quantitative, qualitative and comparative analysis of the portrayal of Ukraine and Ukrainians in the Slovak media, shedding light on the nuanced dynamics of cross-border perceptions and media representations. The main method of research was a content analysis of two Slovak media – Denník N and Hospodárske noviny.  The print and online versions of these media were examined for November and December 2022 and 2023, and April 2024. In total, 600 publications were examined in detail (N = 600). The findings reveal a complex and multifaceted picture of how Ukraine and its people are depicted in the Slovak media. The analysis identifies recurring themes of the war in Ukraine from different aspects, such as the situation on the battlefield, the humanitarian crisis, the attitude to the refugees, etc. The typical topics, genres as well as the image of Ukrainians are outlined.